2017
DOI: 10.1016/j.euromechsol.2016.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Strain localization and ductile fracture in advanced high-strength steel sheets

Abstract: An experimental-numerical approach is applied to determine the strain localization and ductile fracture of high-strength dual-phase and martensitic steel sheet materials. To this end, four different quasi-static material tests were performed for each material, introducing stress states ranging from simple shear to equi-biaxial tension. The tests were analysed numerically with the nonlinear finite element method to estimate the failure strain as a function of stress state. The effect of spatial discretization o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 46 publications
0
25
0
Order By: Relevance
“…For all tests, it is difficult and not possible to capture the exact initial failure location for the tension‐shear specimen. Based on previous studies, the potential failure location of tension‐shear specimen is assumed to be at the centre point of the minimum notch section (see Figure ). The displacement to fracture is determined by the force‐displacement results.…”
Section: Resultsmentioning
confidence: 99%
“…For all tests, it is difficult and not possible to capture the exact initial failure location for the tension‐shear specimen. Based on previous studies, the potential failure location of tension‐shear specimen is assumed to be at the centre point of the minimum notch section (see Figure ). The displacement to fracture is determined by the force‐displacement results.…”
Section: Resultsmentioning
confidence: 99%
“…While the bifurcation analysis has been widely used in the literature, as for instance in Besson et al (2001), Chalal and Abed-Meraim (2015) and Haddag et al (2009) in the context of ductile fracture, the imperfection analysis is less frequently used as a qualitative way of understanding ductile failure. However, some notable studies adopting the imperfection analysis to investigate strain localization are those of Yamamoto (1978), Needleman and Rice (1979), Hutchinson and Tvergaard (1981), Saje et al (1982), Mear and Hutchinson (1985), Nahshon and Hutchinson (2008) and Gruben et al (2017). To trigger localization in a material at reasonable stresses, a softening mechanism must be present in the constitutive equations of the material (Rudnicki and Rice 1975) when the inelastic flow is associative as commonly assumed for metals that are investigated here.…”
Section: Introductionmentioning
confidence: 99%
“…While porous plasticity models can be directly used in numerical simulations of structural components to study the structural response, such models also serve as a means to account for material softening in the strain localization analyses. Previous studies using the imperfection band approach have demonstrated its capabilities as a predictive tool in some specific cases [35,36] but have largely been focused on rateindependent material behavior [35][36][37][38]. Strain localization in ratedependent materials was examined by Pan et al [31] and their results display pronounced effects of rate sensitivity on the failure strain.…”
Section: Introductionmentioning
confidence: 99%